Giải các phương trình sau:
a) \(\sqrt{3x^2-12x+16}+\sqrt{y^2+14y+13}=5\)
b) x+y+z+4 = \(2\sqrt{x-2}+4\sqrt{y-3}+6\sqrt{z-5}\)
Giải phương trình:
\(a)\sqrt{x^2+2x+4}\ge x-2\\ b)x=\sqrt{x-\frac{1}{x}}+\sqrt{x+\frac{1}{x}}\\ c)\sqrt{x+2+3\sqrt{2x-5}}+\sqrt{x-2\sqrt{2x-5}}\\ d)x+y+z+4=2\sqrt{x-2}+4\sqrt{y-3}+6\sqrt{z-5}\\ e)\sqrt{x}+\sqrt{y-1}+\sqrt{z-2}=\frac{1}{2}\left(x+y+z\right)\)
giải phương trình x+y+z+4=\(2\sqrt{x-2}\)+ \(4\sqrt{y-3}\)+ \(6\sqrt{z-5}\)
Giải hệ phương trình: \(\hept{\begin{cases}x+y+z=6\\x^2+y^2+z^2=18\\\sqrt{x}+\sqrt{y}+\sqrt{z}=4\end{cases}}\)
Giải hệ phương trình : \(\hept{\begin{cases}x+y+z=6\\x^2+y^2+z^2=18\\\sqrt{x}+\sqrt{y}+\sqrt{z}=4\end{cases}}\)
Giair phương trình:
\(x+y+z+4=2\sqrt{x-2}+4\sqrt{y-3}+6\sqrt{z-5}\)
Giải hệ phương trình:
\( \begin{cases} x+y+z=6 \\ x^2+y^2+z^2=18, \\ \sqrt{x}+\sqrt{y}+\sqrt{z}=4 \end{cases}\)
Giải phương trình :
\(a,13x-2\sqrt{x}.\left(3+2y\right)+y^2+1=0\)
\(b,x+4\sqrt{x+3}+2\sqrt{3-2x}=11\)
\(c,x+y+z+4=2\sqrt{x-2}+4\sqrt{y-3}+6\sqrt{z-5}\)
\(d,2x+2y+2z=\sqrt{4x-1}+\sqrt{4y-1}+\sqrt{4z-1}\)
Giaỉ phương trình:
1, x + y + 12= 4\(\sqrt{x}+6\sqrt{y-1}\)
2, \(x+y+z=2\sqrt{x-1}+2\sqrt{y-5}+2\sqrt{z+3}\)
3, \(\sqrt{3x^2+12x+13}+\sqrt{4x^2+16x+25}=-x^2-4x\\\)
4, \(\sqrt{x+3-4\sqrt{x-1}}+\sqrt{x+8+6\sqrt{x-1}}=5\)